(untitled) (Bulletin of criminological association of Ukraine, 2024)
This article reveals the psychological factors behind deviant behavior among military personnel in the context of extreme existential trials of war. Offenses in the army are most often explained by two reasons: first, the specifics of military service, such as problems of subordination and the need for strict compliance with military regulations and orders; and second, combat trauma. The most common types of crimes committed by military personnel in the context of Russia’s large-scale aggression against Ukraine are disobedience, leaving one’s post, and desertion. It is №ted that, in wartime, there is a general decline in positive attitudes toward the law among all groups of military personnel. Moral and combat traumatization, increased physical and mental stress associated with understaffed military units, low motivation and morale among servicemen, and doubts about commanders’ professional competence can lead №t only to depression and mental disorders but also to suicide and severe delinquent behavior. When assessing the risk of addictive behavior in servicemen, it is necessary to consider the factors that determine traumatic experiences. These factors include combat operations, threats to life, the death or injury of fellow servicemen or other people, direct clashes with the enemy, injuries, working with the dead, coming under fire, and the duration of time spent in the combat zone.